2018
DOI: 10.1590/1414-431x20176536
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CHCHD4P4 promotes epithelial-mesenchymal transition and inhibits cell proliferation in calcium oxalate-induced kidney damage

Abstract: Kidney stone disease is a major cause of chronic renal insufficiency. The role of long non-coding RNAs (lncRNAs) in calcium oxalate-induced kidney damage is unclear. Therefore, we aimed to explore the roles of lncRNAs in glyoxylate-exposed and healthy mouse kidneys using microarray technology and bioinformatics analyses. A total 376 mouse lncRNAs were differentially expressed between the two groups. Using BLAST, 15 lncRNA homologs, including AU015836 and CHCHD4P4, were identified in mice and humans. The AU0158… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…Over the past decade, LncRNAs, which are members of the noncoding RNA family, have been well‐accepted as crucial biological RNAs in a wide variety of cancerous and noncancerous diseases rather than transcriptional ‘noise’ or cloning artefacts . In a previous study, we identified several CaOx stone‐related lncRNAs using a microarray technique and demonstrated that lncRNA CHCHD4P4 promoted renal EMT in CaOx nephrolithiasis . Another lncRNA, HOXA11‐AS, has been found to have multiple biological functions in a great deal of diseases in recent years .…”
Section: Discussionmentioning
confidence: 96%
“…Over the past decade, LncRNAs, which are members of the noncoding RNA family, have been well‐accepted as crucial biological RNAs in a wide variety of cancerous and noncancerous diseases rather than transcriptional ‘noise’ or cloning artefacts . In a previous study, we identified several CaOx stone‐related lncRNAs using a microarray technique and demonstrated that lncRNA CHCHD4P4 promoted renal EMT in CaOx nephrolithiasis . Another lncRNA, HOXA11‐AS, has been found to have multiple biological functions in a great deal of diseases in recent years .…”
Section: Discussionmentioning
confidence: 96%
“…In recent years, lncRNAs have been a hot point in the research of developmental processes and disease states as a potentially novel and crucial layer of biological regulation . Several studies have reported that dysregulation of lncRNAs might induce multiple diseases, such as diabetes, kidney dysfunction, cardiovascular diseases, and malignant tumors . The role of lncRNAs in cancer has been the focus of this research .…”
Section: Discussionmentioning
confidence: 99%
“…19 Several studies have reported that dysregulation of lncRNAs might induce multiple diseases, such as diabetes, kidney dysfunction, cardiovascular diseases, and malignant tumors. [20][21][22][23] The role of lncRNAs in cancer has been the focus of this research. 24 However, little is known about the role of lncRNAs in GEP-NENs.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences have found that many lncRNAs are aberrantly expressed in various diseases including cancers . Furthermore, functional studies of lncRNAs have highlighted the fact that many lncRNAs have crucial roles in a diverse array of diseases including cancers …”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] Furthermore, functional studies of lncRNAs have highlighted the fact that many lncRNAs have crucial roles in a diverse array of diseases including cancers. [20][21][22][23] As to melanoma, several lncRNAs are reported to have functional significances. LncRNA H19 was revealed to promote glucose metabolism and cell growth in melanoma.…”
mentioning
confidence: 99%